2023
DOI: 10.3390/ijms24054875
|View full text |Cite
|
Sign up to set email alerts
|

High-Molecular-Weight Exopolysaccharides Production from Tuber borchii Cultivated by Submerged Fermentation

Abstract: Truffles are known worldwide for their peculiar taste, aroma, and nutritious properties, which increase their economic value. However, due to the challenges associated with the natural cultivation of truffles, including cost and time, submerged fermentation has turned out to be a potential alternative. Therefore, in the current study, the cultivation of Tuber borchii in submerged fermentation was executed to enhance the production of mycelial biomass, exopolysaccharides (EPSs), and intracellular polysaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…The amount of glucose used in our system could be high enough to trigger this effect in T. borchii , preventing the accumulation of biomass in this way. Chen et al [ 39 ] observed the best growth in sucrose over glucose in submerged cultures of T. borchii .…”
Section: Discussionmentioning
confidence: 99%
“…The amount of glucose used in our system could be high enough to trigger this effect in T. borchii , preventing the accumulation of biomass in this way. Chen et al [ 39 ] observed the best growth in sucrose over glucose in submerged cultures of T. borchii .…”
Section: Discussionmentioning
confidence: 99%
“…The polysaccharide (PSH) extracts were prepared following a modified method outlined by Chen et al [19]. PSH extracts from both S. commune strains (SRB and ITA) were simultaneously extracted to obtain exo-polysaccharide (EPSH) from the filtrate (F) and intra-polysaccharide (IPSH) from the mycelia biomass (BM).…”
Section: Fungal Cultivation and Polysaccharide Extraction Processmentioning
confidence: 99%
“…For the bioconversion of organic wastes including agro-industrial lignocellulose wastes, hydrolytic enzymes called hydrolases are often utilized [ 23 , 26 , 32 , 105 , 106 ]. Since the enzymatic process operates under mild reaction conditions without the use of hazardous chemicals, it is more conducive to the idea of a biodegradable process for XOS production.…”
Section: Enzymatic Hydrolysis Of Xylan For Xylooligosaccharides Produ...mentioning
confidence: 99%